KELEMBAGAAN PENDIDIKAN - Paulus Satyo Istandar Tan (LPPM Politeknik Saint Paul Sorong, 2021)
One factor that greatly affects the quality of education delivery is the organization or institution of education delivery. This problem has implications for ineffective and inefficient education management processes. The research method used is a qualitative description method by collecting library data, reading and recording and processing research materials. Education is the whole praxis of life and processes of events accompanied by reflection both spontaneous and systematic. The essence of education is liberating human intelligence (humanization).